Diseño de un centro de acopio de residuos de aparatos eléctricos y electrónicos (RAEE), empleando logística inversa - ciudad de Tunja (2021)
The rise of the revolution 4. 0 and the pandemic COVID - 19, gave emphasis to the commercialization of electronic and electrical devices on a large scale deriving in turn an increase in the change of technology in industries and homes of all their technological equipment, which brought with it an increase in the generation of electronic and electrical waste; The city of Tunja Boyacá is not indifferent in the production of this waste, so one of the main objectives of the development of this project is to undertake with a collection center for the management of the same, implementing reverse logistics and contributing to the reduction of environmental and socio-cultural impacts of the city.